Do teacher related factors play a role in laptop use for teaching-learning? - Wong, Su Luan; Moses, Priscilla (UHAMKA Press, 2013)
Equipping laptops to Malaysian teachers is a much needed step to advance the education system. Central to this, teachers must be recognized as the change agent in the successful use of laptops and ICT innovation in schools. This study was conducted to explore the overall profile of teachers’ laptop use and also to investigate if selected teacher related factors (age, gender, teaching experience, laptop experience, attitudes towards laptop use and laptop skills) play a role in laptop use for teaching-learning. A total of 463 teachers participated in this study and the findings indicate that teachers are not using laptops as much as they should in the classrooms. The findings also suggest that four teacher related factors (gender, laptop experience, attitudes towards laptop use and laptop skills) play a significant role in teachers’ laptop use for teaching-learning.